Effect of stress on the paracellular barrier in the rat ileum. Issue 4 (1st October 2002) - Mazzon, E; Sturniolo, G C; Puzzolo, D; Frisina, N; Fries, W
Abstract : Background: Restraint stress induces permeability changes in the rat small intestine but little is known of the ultrastructural events leading to defects of the paracellular sealing or of the short term evolution of these alterations. Methods: In the present study, we performed transmission electron microscopy in the terminal ileum perfused with lanthanum after two hours of immobilisation stress and in non-stressed control rats. Moreover, immunohistochemistry of the tight junction (TJ) associated proteins, occludin and zonula occludens 1 (ZO-1), was carried out together with western blot analysis of the transmembrane protein occludin. TJ morphology was also assessed after a 22 hour recovery period. Results: Immobilisation stress induced a significant increase in epithelial permeability to the lanthanum tracer (p<0.005) which recovered completely after 22 hours. Compared with unstressed controls, in stressed rats no differences were found on freeze fracture analysis. The TJ related immunofluorescence signals of occludin and of ZO-1 were irregularly distributed in stressed rats after two hours but returned to a normal pattern at 24 hours although with minor intensity. No quantitative alterations in occludin were detectable in stressed rats by immunoblot whereas a perinuclear concentration of occludin was observed by immunolocalisation. Conclusions: Immobilisation stress induced an increase in TJ permeability in the rat terminal ileum. These changes were mainly due to modifications and redistribution of the TJ transmembrane protein occludin and of the plaque protein ZO-1 whereas protein synthesis, at least that of occludin, was not affected by stress.